Współczesne reminiscencje absolutystycznego modelu policji administracyjnej - Małecki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The absolutist model of administrative police, perceived as a sphere of the activity of public authority, is based on two pillars. The material pillar concerns the purpose of police activity, which is to achieve overall prosperity including the prosperity individuals, in the shape specified by the monarch. The formal pillar concentrates on ius politiae — the general authorization of the monarch to perform each forcible interference in the sphere of the rights of the subject, intended to achieve overall and individual prosperity. Contemporary institution of forced evacuation corresponds to the material pillar of the absolutist model of administrative police, as it allows public authority to evacuate an individual in case of threat for their life, even despite the opposition of the individual. The institution of order regulations seems to be a contemporary reminiscence of ius politiae. In the form of order regulations the organs of public administration, using a general competence, are entitled to establish legal norms, the content of which is not specified in the statute.
Keywords: policja administracyjna; przymusowa ewakuacja; przepisy porządkowe